THE GAME AND ITS SOCIAL-CULTURAL CONTRIBUTION FOR EDUCATION AND PHYSICAL EDUCATION (Fiep Bulletin - online, 2011)
This text results from studies performed in the Sportiveness and Physical Education research group, linked to ETHNÓS (ESEF-UPE-BRASIL). We researched the presence of the game as a social-cultural phenomenon through the identification and understanding of its main characteristics, conception and its relationship with culture, society and education, identifying how these comprehensions are present in practice, or be, at school, especially in Physical Education classes. Regardless of time, culture, and social class, games and jokes have always been present in human beings' life. We believe game is an important means for children and youths' formation. For this reason, it is imperative to search the sportiveness understanding according to philosophical and pedagogical aspects, reflecting about the practice so that we can perceive game as an essential knowledge for education and Physical Education.
Keywords: game; culture; physical education